2012
DOI: 10.1094/mpmi-05-11-0138
|View full text |Cite
|
Sign up to set email alerts
|

Flagella Mediate Endophytic Competence Rather Than Act as MAMPS in Rice–Azoarcus sp. Strain BH72 Interactions

Abstract: Azoarcus sp. strain BH72 is an endophytic betaproteobacterium able to colonize rice roots without induction of visible disease symptoms. BH72 possesses one polar flagellum. The genome harbors three copies of putative fliC genes, generally encoding the major structural protein flagellin. It is not clear whether, in endophytic interactions, flagella mediate endophytic competence or act as MAMPs (microbe-associated molecular patterns) inducing plant defense responses. Therefore, possible functions of the three Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 47 publications
0
35
0
1
Order By: Relevance
“…strain BH72 [35], [36], [37]. Enhancement of expression of pilH , pilY1B and fliF under diazotrophic growth (Table S1) speaks in favor of a common mode of gene regulation.…”
Section: Resultsmentioning
confidence: 98%
“…strain BH72 [35], [36], [37]. Enhancement of expression of pilH , pilY1B and fliF under diazotrophic growth (Table S1) speaks in favor of a common mode of gene regulation.…”
Section: Resultsmentioning
confidence: 98%
“…For example, the lack of flagella might decrease the defense response and improve endophytic colonization, an observation reported for a mutant of Salmonella in A. thaliana (53). Contradictory studies showed that in the rice-Azoarcus system, flagella are required for efficient colonization rather than act as MAMPs (21). The so-far limited studies suggest that endophytes induce only low levels of defense responses in compatible interactions (71), mostly from the JA pathway (1, 71), and they might even trigger specialized signaling cascades, but the mechanisms are still obscure (17,26,85).…”
Section: The Plant Innate Immune Response In Beneficial Interactionsmentioning
confidence: 90%
“…A pilT mutant of Azoarcus sp. BH72, which still produced pili but was not capable of twitching motility, was particularly impaired in endophytic colonization but still colonized the root surface (16); likewise, a mutant lacking flagella was retarded only in endophytic colonization (21). Thus, some traits for rhizoplane and endorhizosphere colonization may be different from each other.…”
Section: Into the Roots: Ways Endophytes Get Inmentioning
confidence: 99%
See 1 more Smart Citation
“…strain BH72 to establish inside rice roots but this was not important for the colonization on the root surface (Böhm et al, 2007). For beneficial endophytes, the bacterial flagella that typically act as a potent microbe-associated molecular pattern (MAMP) for recognition by the innate immune system may instead mediate endophytic competence by enabling bacterial chemotactic movement and anchoring to plant surfaces (Buschart et al, 2012). The five endophytic bacteria examined by Straub et al (2013) all contain the entire flagella machinery and a flagella-deficient mutant was hampered in colonization efficiency of wheat roots (Croes et al, 1993).…”
Section: Traits For Successful Invasion Colonization and Translocatimentioning
confidence: 99%